Analisis Interaksi Obat pada Pasien Hipertensi di Posyandu Lansia Lembaga Kartini Surya Khatulistiwa Tanjung Hilir - Raine Ardhita Anggraeny; Syarifah NYRS Asseggaf; Nurmainah Nurmainah (Wal'afiat Hospital Journal, 2025)
Polypharmacy of drugs in elderly hypertensive patients cannot be avoided because the elderly have several diseases other than hypertension. Polypharmacy administration of drugs can increase the potential for drug interactions to occur at a major, moderate or minor level, as well as occur in the pharmacodynamic or pharmacokinetic phase. One way that can be done to reduce these risks is by administering the right medication and minimizing the administration of polypharmacy for hypertensive patients. The research to analyze interactions between drugs, classify antihypertensive drugs, describe the percentage of drug interactions, and the severity of drug interactions given to elderly hypertensive posyandu patients at the Kartini Surya Khatulistiwa Tanjung Hilir Society. Observational with a descriptive model of the cross-sectional study. The sample used in this study is 36 hypertensive patients at the Posyandu Lansia Lembaga Kartini Surya Khatulistiwa Tanjung 2019. This research was conducted from March-April 2021. Samples are selected using Consecutive Sampling (nonprobability sampling). 79 cases interaction drug of hypertension patients in Posyandu Lansia Lembaga Kartini Surya Khatulistiwa Tanjung Hilir Drug interactions that occurred moderate level were 47 cases (59%) and pharmacodynamic stage in 71 cases (90%).